2020
DOI: 10.1016/j.neuropsychologia.2020.107343
|View full text |Cite
|
Sign up to set email alerts
|

Resting-state EEG reveals global network deficiency in dyslexic children

Abstract: Developmental dyslexia is known to involve dysfunctions in multiple brain regions; however, a clear understanding of the brain networks behind this disorder is still lacking. The present study examined the functional network connectivity in Chinese dyslexic children with resting-state electroencephalography (EEG) recordings. EEG data were recorded from 27 dyslexic children and 40 age-matched controls, and a minimum spanning tree (MST) analysis was performed to examine the network connectivity in the delta, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 67 publications
1
36
1
Order By: Relevance
“…The lower levels of neural entrainment and connectivity may reflect the effects of a disrupted neural network structure and mixed patterns of connectivity abnormalities in children with dyslexia (Frye et al, 2012;Koyama et al, 2013). Similar effects were found in resting-state experiments, where typically developing children presented higher levels of connectivity than the children with dyslexia in the theta frequency band (Fraga González et al, 2016;Xue et al, 2020). Strong compensatory mechanisms seem to appear in later stages of development.…”
Section: Connectivitymentioning
confidence: 52%
See 1 more Smart Citation
“…The lower levels of neural entrainment and connectivity may reflect the effects of a disrupted neural network structure and mixed patterns of connectivity abnormalities in children with dyslexia (Frye et al, 2012;Koyama et al, 2013). Similar effects were found in resting-state experiments, where typically developing children presented higher levels of connectivity than the children with dyslexia in the theta frequency band (Fraga González et al, 2016;Xue et al, 2020). Strong compensatory mechanisms seem to appear in later stages of development.…”
Section: Connectivitymentioning
confidence: 52%
“…Typical readers show a higher phase coherence at the age of 7 while children with dyslexia have a higher phase coherence at the age of 9. Higher levels of connectivity in beta oscillations for children older than 8 years with dyslexia have also been reported in resting-state studies (Xue et al, 2020) and are present in adolescence (Granados Barbero et al, 2021b) and in adulthood (Thiede et al, 2020). This later maturation of beta oscillations found with connectivity may trigger the compensatory mechanisms in the neural entrainment levels (SNRs) that appear in adolescents (Granados Barbero et al, 2021b) and adults (Helenius et al, 2002).…”
Section: Activity At 20 Hz (Beta Rhythm)mentioning
confidence: 68%
“…Applying this method to resting-state EEG data, our child study revealed statistically significant group differences in the theta (4–8 Hz) band suggesting reduced network integration and less communication between network nodes in children with dyslexia compared to typical readers ( Fraga González et al, 2016 ). A similar study used the same approach on Chinese-speaking children of similar age and found differences between dyslexic and typical readers in the same direction but in MST metrics in the beta band ( Xue et al, 2020 ). They used shorter epoch length and a smaller montage with less electrodes compared to our previous study, which may have contributed to the differences in addition to the different alphabetic systems.…”
Section: Introductionmentioning
confidence: 93%
“…Fraga González and others found dyslexic children to have a significantly lower leaf fraction and higher diameter in EEG theta band than typically reading children ( Fraga González et al, 2016 ), while Xue and others found no significant differences ( Xue et al, 2020 ). Fraga González and others found a higher kappa in dyslexic young adults ( Fraga González et al, 2018 ).…”
Section: Resultsmentioning
confidence: 97%